Medicalisation of Birth in Transylvania in the Second Half of the 19th Century. A Subject to be Investigated - Luminiţa Dumănescu; Ioan Bolovan (Historical Life Course Studies)
The role played by midwives during modernity deserves increased attention. Ethnic and confessional minorities often displayed starkly different patterns in the selection of these instrumental figures. More than that, the differences between the official reports and the community behavior recorded at ground level suggest a major gap between theory and practice. In theory, the province of Transylvania was well provided with medical care, midwives included. Data collected into the Historical Population Database of Transylvania reveals the fact that most women were assisted at birth by handywomen, the traditional, unskilled midwives. A research tool like a historical population database could help the scholars to address the issue of birth medicalisation, starting from the main research question: can we discuss the medicalisation of birth given that more than half of the women assisted in the delivery of just one child?